Adsorption Studies of Acetic Acid on the Surface of Alternenthera triandra - Hussain, Sayyed; Farooqui, Mazhar; Shookur, M.A. (Asian Journal of Chemistry, 2016)
The adsorption of acetic acid on Alternenthera triandra using batch adsorption process has been investigated. The effect of certain parameters on adsorption has been studied. Applicability of Freundlich adsorption isotherm and Langmuir adsorption isotherm has also been tested. Various thermodynamic parameters such as DG, DH and DS are reported.